Step‐by‐Step Strategy for Constructing Multilayer Structured Coatings toward High‐Efficiency Electromagnetic Interference Shielding. Issue 5 (7th January 2016) - Zou, Lihua; Zhang, Songlin; Li, Xiangpeng; Lan, Chuntao; Qiu, Yiping; Ma, Ying
Abstract : A simple and versatile step‐by‐step strategy is utilized to construct multilayer structured coatings for high‐efficiency electromagnetic interference (EMI) shielding. The step‐by‐step construction realizes the excellent and controllable EMI shielding as well as fast thermal dissipation and satisfied stability. This work demonstrates the advantages of nanostructure in EMI shielding and provides a new strategy for designing high‐performance shielding materials.